Hormonal-Induced Cervical Relaxation During Diestrus in Ewes: Cervical Transposing Feasibility and Use of hCG for Rescuing Disrupted Luteal Function - Oliveira, Maria Emilia Franco [UNESP]; Arrais, Aline Matos; Vergani, Gabriel Brun [UNESP]; Novita Esteves, Sergio; Schinaider Do Amaral Pereira, Verônica; Garcia, Alexandre Rossetto; Bastos, Rosemary; Roberto Bourg Melo, Marco; Rios Coelho Alves, Bruna; Ferreira Fonseca, Jeferson (Taylor & Francis, 2022)
Cervical relaxation (CR) was performed in ewes during diestrus, to prospect a feasible protocol for non-surgical embryo transfer (NSET). In Trial 1, naturally mated ewes (n=13) received CR protocols with estradiol benzoate (EB, 1 mg on D6) and oxytocin (OT, 50 IU on D7) only (G-EB+OT) or associated with human chorionic gonadotropin (hCG, 300 IU on D7, G-EB+OT+hCG) and were compared to non-hormonally treated (G-control) ewes. Estradiol concentration increased (P<0.05) from D6 to D7 in G-EB+OT and G-EB+OT+hCG, then decreased (P<0.05) on D8. The G-EB+OT had reduced (P<0.05) progesterone on D8, and 0% (0/5) pregnancy, while G-control had 100% (3/3) conception rate. The treatment with hCG mitigated the progesterone drop on D8 and resulted in 50% (2/4) conception rate. In Trial 2, cervical transposing success after treatment with EB, OT, and hCG on D6 and D7 was assessed in nulliparous (n=25) and multiparous (n=30) ewes. The EB+OT+hCG protocol allowed efficient cervical transposition (~78% of cervical transposition success into ~5 min) in nulliparous and multiparous females and did not alter total and blood perfusion areas of corpora lutea (CL). The use of EB+OT+hCG was efficient to ensure effective cervical transposing in nulliparous and multiparous ewes, with no apparent deleterious effect on CL function, and may contribute to animal welfare, allowing a less invasive NSET procedure.
Keywords: animal welfare; Embryo transfer; non-surgical; pharmacological; transcervical